The Role of International Organizations in Promoting Human Rights Enforcement and Global Peace: A Study on the Middle East - Agustinus Santiago Eca Fernandes (International Journal of Education, Vocational and Social Science, 2025)
International organizations play a crucial role in protecting human rights (HR) and achieving peace worldwide. The United Nations (UN), the Arab League, and non-governmental organizations (NGOs) have worked to stop human rights violations and widespread conflicts in various regions, including the Middle East. However, resource limitations, political interests of member states, and the lack of enforcement mechanisms often hinder their effectiveness. Ongoing conflicts in the Middle East, such as the Syrian war and the Israel-Palestine tensions, demonstrate that international interventions have still been unable to bring lasting stability. Despite various policies, such as diplomatic resolutions, peace missions, and humanitarian aid, the results have been limited. One of the major issues faced is the obstruction of neutral conflict resolution efforts by global political interests. Additionally, there is resistance from the warring parties and a lack of coordination between local actors and international organizations. If international organizations wish to enhance their ability to address conflicts in the Middle East, they must take strategic actions, such as increasing sanctions against human rights violators, improving rapid responses to conflicts, strengthening cooperation with local actors, maintaining integrity and accountability, and implementing an inclusive peace approach. International organizations can enforce human rights and create more sustainable global peace by adopting a more flexible approach and collaborating.